Impact of introducing assisted electronic prescription on paediatric patient safety - Carla Fernández-Oliveira; Cristina Martínez-Roca; Alejandro Ávila-Álvarez; Vanesa Balboa-Barreiro; Víctor Giménez-Arufe; Pedro Yáñez-Gómez; María Carmen Hermida-Bouzas; Isabel Martín-Herranz (Elsevier, 2020)
Objective: There have been very few studies on the effect of assisted electronic prescription on paediatric patient safety. The objective of this study is to compare medication errors that occurred before and after its introduction in a tertiary hospital. Materials and methods: A quasi-experimental comparative study of medication errors detected before and after assisted electronic prescription introduction. All treatment lines were analysed in order to detect the point in the chain where the medication error occurred, as well as its type and cause. A Delphi study was conducted on the importance of each medication error involving doctors, nurses and pharmacists. Results: The study included 166 patients (83 at each stage). At least one medication error was detected in 92% in the pre-introduction phase patients (2.8 ± 2.1 errors/patient) and 7.2% of post-introduction phase patients (0.1 ± 0.4 errors/patient). The assisted electronic prescription led to an absolute risk reduction of 40% (95% confidence interval = 35.6-44.4%). The main cause of error was lapses and carelessness in both stages. Medication errors were considered serious in 9.5% of cases in the pre-introduction phase, while all of them were mild or moderate in the post-introduction phase. Conclusions: The assisted electronic prescription implementation with prescription, validation and medication administration assistance systems significantly reduces medication errors and eliminates serious errors. Resumen: Objetivo: El efecto de la implantación de la prescripción electrónica asistida en la seguridad de los pacientes pediátricos ha sido poco estudiado. El objetivo de este estudio es comparar los errores de medicación antes y después de su implantación en un hospital terciario. Material y métodos: Estudio cuasiexperimental comparativo de los errores de medicación detectados, antes y después, de la implantación de la prescripción electrónica. Se analizaron todas las líneas de tratamiento y se recogió el punto de la cadena donde ocurrió el error, el tipo de error y su causa. Se realizó un estudio Delphi sobre la importancia de cada error en el que participaron médicos, enfermeros y farmacéuticos. Resultados: Se incluyeron 166 pacientes (83 en cada etapa). Se detectó algún error en el 92% de los pacientes en la etapa preimplantacional (2,8 ± 2,1 errores/paciente) y en el 7,2% en la etapa postimplantacional (0,1 ± 0,4 errores/paciente). La prescripción electrónica asistida supuso una reducción absoluta del riesgo de error de un 40% (95% intervalo de confianza = 35,6 - 44,4%). Los lapsus/despistes fueron la principal causa de error en ambos grupos. En la etapa preimplantacional se consideraron graves el 9,5% de los errores y, en la etapa postimplantacional, todos fueron leves o moderados. Conclusiones: La implantación de la prescripción electrónica con sistemas de ayuda a la prescripción, validación y administración de medicamentos reduce de forma significativa los errores de medicación y elimina los errores graves.